Impaired sensorimotor integration in focal hand dystonia patients in the absence of symptoms. Issue 6 (3rd December 2009) - Wu, C Carolyn; Fairhall, Scott L; McNair, Nicolas A; Hamm, Jeff P; Kirk, Ian J; Cunnington, Ross; Anderson, Tim; Lim, Vanessa K
Abstract : Background: Functional imaging studies of people with focal hand dystonia (FHD) have indicated abnormal activity in sensorimotor brain regions. Few studies however, have examined FHD during movements that do not provoke symptoms of the disorder. It is possible, therefore, that any differences between FHD and controls are confounded by activity due to the occurrence of symptoms. Thus, in order to characterise impairments in patients with FHD during movements that do not induce dystonic symptoms, we investigated the neural correlates of externally paced finger tapping movements. Methods: Functional MRI (fMRI) was used to compare patients with FHD to controls with respect to activation in networks modulated by task complexity and hand used to perform simple and complex tapping movements. Results: In the 'complexity network, ' patients with FHD showed significantly less activity relative to controls in posterior parietal cortex, medial supplementary motor area (SMA), anterior putamen and cerebellum. In the 'hand network, ' patients with FHD showed less activation than controls in primary motor (M1) and somatosensory (S1) cortices, SMA and cerebellum. Conjunction analysis revealed that patients with FHD demonstrated reduced activation in the majority of combined network regions (M1, S1 and cerebellum). Conclusion: Dysfunction in FHD is widespread in both complexity and hand networks, and impairments are demonstrated even when performing tasks that do not evoke dystonic symptoms. These results suggest that such impairments are inherent to, rather than symptomatic of, the disorder.